New England Telephone, 10 Cambridge Street, December 4, 1960 - Fay Foto Service Inc. (Tufts Archival Research Center, 2005)
Street-level view looking northeast from Bowdoin Square of the New England Telephone building in the West End. A few cars are parked along the sidewalk. 9 1/2 x 7 5/8 overall 10 x 8 Photographs